The effect of training, work motivation, and employee engagement on employee work productivity at the Population and Civil Registration Office, Humbang Hasundutan - Lumbantoruan, Putri L.; Panjaitan, Maludin; Rajagukguk, Tiur (Jurnal Bisnis Mahasiswa, 2025)
This study aims to investigate and analyze the impact of training, work motivation, and employee engagement on the work productivity of employees at the Humbang Hasundutan Population and Civil Registration Office. The type of research used in this study is quantitative research. The sample in this study was 45 respondents.  Based on the results of the hypothesis test, it can be concluded that training, work motivation, and employee engagement have a positive and significant effect on work productivity. Based on the results of the hypothesis test F, it is concluded that training, work motivation, and employee engagement together or simultaneously have a significant effect on work productivity.  Based on the results of the analysis of the determination coefficient, it is known that the value of the determination coefficient (adjusted R-square) is 0.725. Based on this value, training, work motivation, and employee engagement were able to affect work productivity by 72.5%; other variables or factors explained the remaining 27.5%.